SENGKETA WARIS TERHADAP HARTA PENINGGALAN ALMH. JENNY THE (STUDI KASUS PUTUSAN NOMOR 410/PDT.G/2020/PN MND) - Fara Dinda Fasya; Suparsetyani , Endang (Reformasi Hukum Trisakti, 2023)
According to the Civil Code, the death of a person will open up inheritance for his heirs. The formulation of the problem raised in the journal is how to distribute the assets of the deceased. Jenny The to his heirs according to the Civil Code and the contents of Ruling numbers 2 and 3 regarding the determination of the heirs of the deceased. Jenny The in Manado District Court decision No. 410/Pdt.G/2020/PN.MND is appropriate or not according to the Civil Code. In order to be able to answer this the research method uses a normative juridical type, the nature of the research used is analytical descriptive, the data used is secondary data, data analysis is done qualitatively, and conclusions are drawn using deductive logic methods. The results of the research and discussion of this journal are related to the death of the late Almh. Jenny The, who opened up the occurrence of inheritance to his heirs and caused disputes between them. The conclusion is that Krusteddy gets 1/3 of the share, because Krusteddy has died then his share will be replaced by Melissa and Christian who each get 1/6 of the share, then Rudy Lo gets 1/3 of the share, and Agustina gets 1/3 of the share as well as the contents of the rulings number 2 and 3 regarding the determination of the heirs of the deceased. Jenny The in Manado District Court decision No. 410/Pdt.G/2020/PN.MND according to the Civil Code.